Tumor necrosis factor SNP haplotypes are associated with iron deficiency anemia in West African children. - Atkinson, S; Rockett, K; Morgan, G; Bejon, P; Sirugo, G; O'Connell, M; Hanchard, N; Kwiatkowski, D; Prentice, A (2008)
Plasma levels of tumor necrosis factor-alpha (TNF-alpha) are significantly raised in malaria infection and TNF-alpha is thought to inhibit intestinal iron absorption and macrophage iron release. This study investigated putative functional single nucleotide polymorphisms (SNPs) and haplotypes across the major histocompatibility complex (MHC) class III region, including TNF and its immediate neighbors nuclear factor of kappa light polypeptide gene enhancer in B cells (lkappaBL), inhibitor-like 1 and lymphotoxin alpha (LTA), in relation to nutritional iron status and anemia, in a cohort of 780 children across a malaria season. The prevalence of iron deficiency anemia (IDA) increased over the malaria season (P < .001). The TNF(-308) AA genotype was associated with an increased risk of iron deficiency (adjusted OR 8.1; P = .001) and IDA (adjusted OR 5.1; P = .01) at the end of the malaria season. No genotypes were associated with IDA before the malaria season. Thus, TNF appears to be a risk factor for iron deficiency and IDA in children in a malaria-endemic environment and this is likely to be due to a TNF-alpha-induced block in iron absorption.